The application of on training monitoring digital model for effectiveness maritime cadets on board training activities - Wahdiana, Dian; Ekohariadi, Ekohariadi; Suhartini, Ratna (Edelweiss Applied Science and Technology, 2025)
Effective monitoring of On-Board Training (OBT) activities is essential in maritime seamanship education to ensure cadets develop the necessary competencies and problem-solving abilities. Traditional monitoring methods often lack real-time tracking, structured feedback, and comprehensive evaluation; therefore, there is a need for an On-Training Monitoring Application model. On-Training Monitoring is a digital monitoring application designed to improve training supervision, structured feedback, and evaluation of cadet performance during OBT. This study aims to assess the On-Training Monitoring application to enhance cadets' competence and problem-solving abilities during OBT. The research is based on experiential learning theory and competency-based training models, which emphasize real-time monitoring, systematic feedback, and data-driven evaluation as key factors in improving training outcomes. This study employed a quantitative approach involving maritime cadets and instructors undergoing OBT. Data were collected through a structured survey and system logs from the On-Training Monitoring application. Statistical analysis techniques included descriptive statistics, correlation analysis, and t-tests to evaluate the effectiveness of On-Training Monitoring in improving training outcomes. The results indicated that On-Training Monitoring was able to enhance competency development by providing real-time monitoring and structured feedback, which positively impacted the improvement of problem-solving skills among cadets. The findings offer valuable insights for maritime education institutions regarding the integration of digital monitoring tools such as On-Training Monitoring to improve training supervision and competency assessment. This research contributes to maritime training literature by introducing On-Training Monitoring as an innovative digital monitoring application and demonstrating its effectiveness in improving cadet competencies and problem-solving skills through data-driven training evaluation.